The Concept of Ingrowing in the Theory of Development of Higher Psychological Functions - A.D. Maidansky (Культурно-историческая психология, 2024)
The author examines the concept of ingrowing in Lev Vygotsky’s cultural-historical psychology. The theoretical significance of his metaphors of ingrowing and gardening, and the connection between the terms “ingrowing” and “interiorisation” are revealed. The plain criterion for evaluating the success of ingrowing higher psychological functions is found in the development of verbal thinking. By analysing the concepts of interpsychic and intrapsychic function, the author shows how Vygotsky understands the process of transformation of one function into another: (i) types of ingrowing and (ii) the nature of changes in the structure of higher psychological functions during the transition of interpsychic forms of behaviour into the child’s consciousness. The controversy between Vygotsky and Aleksei Leontiev on the ingrowing of word meanings is discussed. Special attention is paid to the ingrowing scientific concepts at school age. The epilogue briefly outlines the fate of the concepts of ingrowing and interiorisation in Russian cultural-historical psychology.